(untitled) (Third Sector Social Economic Review, 2025)
This study investigates the historical development of public holiday camps, which represent a distinctive manifestation of social tourism in Türkiye. Established by public institutions, organisations, and state economic enterprises to meet the holiday and recreation needs of employees and their families, these camps functioned for many years as spatial extensions of social state policies and played significant social roles. Despite their importance, studies on public holiday camps remain very limited in the literature, with most existing research restricted to statistical data and lacking in-depth examination of their social, cultural, and spatial dimensions. The present study aims to fill this gap by analysing holiday camps not merely as physical spaces, but as implementation arenas of social state policies and institutional instruments of social tourism. Adopting a qualitative research design, the study employs the document analysis technique, systematically examining development plans, official reports, legislative documents, archival materials, and visual sources. The evolution of public holiday camps is explored within a chronological framework based on periodisation, comprising four phases parallel to the development of tourism in Türkiye: the Pre-Planned Period (1923–1963), the Planned Period – Early Phase (1963–1980), the Neoliberal Transition (1980–2000), and the Contemporary Period (post-2000). Findings reveal that while these camps long served as central components of social tourism, neoliberal reforms, privatisation, and societal transformation have led to their gradual functional decline.